Studies On The Genetic Diversity, Distribution And Current Status Of Coelogyne Lindl. (Orchidaceae) Species Of Darjeeling Hills Of West Bengal, India - RAJENDRA YONZONE; D. LAMA; R. B. BHUJEL; SAMUEL RAI (International Journal of Pharma and Bio Sciences, 2012)
Present paper deals the genetic diversity, distribution and current status with habitat, place of occurrence, altitudinal ranges and flowering times of 16 Coelogyne species which are widely distributed throughout the Darjeeling Hills of West Bengal, India. In the present investigation Raunkiaer’s Ecological Statitistics, given by Raunkiaer, (1934) were laid out to findout the current ecological status of these species from Darjeeling Hills. 7 species viz., Coelogyne barbata., C. occultata., C. pantlingii., C. pempahesiana., C. punctulata., C. stricta., and C. viscosa. are rare while 2 species viz., C. corymbosa and C. nitida were placed under frequent category. The species C. cristata was abundant in the region. Coelogyne raizadae and C. ovalis that were found sparsely while 4 species viz., C. fimbriata., C. flacidda., C. fuscescens and C. prolifera are common and found everywhere in the study area.